Efficacy of Cloth Face Mask in Reducing COVID-19 Transmission: A Literature Review - Rizki, Saraswati Anindita; Kurniawan, Andree (Kesmas, 2020)
Coronavirus disease 2019 (COVID-19) has become a public health concern. Preventive measures, such as wearing personal protective equipment, must be done. On April 2020, the Center for Disease Control stated cloth face mask was recommended to be used by the public. This systematic review aimed to eva - luate the efficacy of cloth face masks in reducing COVID-19 transmission and to compare the fabric material that suits best for a cloth face mask. Journals included were from databases such as Google Scholar, PubMed, search engines, and references from other studies. The MeSH keywords, such as "cloth mask efficiency", "surgical mask", "COVID-19" and "filtration performance of common fabrics cloth mask" were used. Studies that used particle microorganisms sized ≤ 0.072 μm were included in this study. Studies showed that cloth face mask still can filter to a certain extent, however, it is inferior compared to surgical mask. Results show that the efficacy of cloth face mask depends on its fabric, and that polyester provides the best filtration efficiency. However, the pressure drop of polyester is unknown and more studies should be done.